The Lack of Evidence for a Jewish Christian Countermission in Galatia - Gregerman, Adam (Studies in Christian-Jewish Relations, 2011)
Most commentators on Paul’s letter to the Galatians have argued that his opponents were competing Jewish Christian missionaries. Fired by zeal to convert the Gentiles similar to Paul’s, these outsiders supposedly meddled in his church by preaching about the necessity of circumcision for salvation. I challenge this portrait and propose an alternative explanation for their demand that Gentile believers be circumcised. Instead of seeing them as interlopers with what some scholars call characteristically Jewish âextremistâ (i.e., restrictive) views of Gentile salvation, I demonstrate that theyâlike nearly all other late Second Temple period Jewsâwere unconcerned with Gentile soteriology. Rather, they were responding to an entirely different development, the influx of unconverted Gentiles into their originally all-Jewish religious movement as a result of Paul’s preaching. They responded as other Jews would respond, by insisting that those who sought to be members of such a community undergo circumcision and observe the Torah. I argue that we can say almost nothing about their views of a mission to the Gentiles and should not presume that their concerns were at all similar to Paul’s, whose zeal to convert Gentiles was unique. My reconstruction draws on recent research on this period demonstrating Jewish opposition to attempts to convert Gentiles, along with a Jewish commitment to maintaining traditional religious boundaries between Jews and non-Jews.